2006
DOI: 10.1253/circj.70.352
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Aging-Associated Trends of the Monophasic Action Potential Duration and Effective Refractory Period of the Right and Left Atria of the Rat

Abstract: SolutionsThe pH of Krebs-Henseleit solution [(mmol/L): NaCl 140, KCl 5.4, MgCl2·5H2O 1.0, CaCl2·2H2O 1.8, glucose 5.0, sodium pyruvate 4.0, tris base 10] was adjusted to 7.4 with HCl, and maintained by equilibration with 5%CO2-95%O2. All reagents were of analytical purity grade. Background The incidence of atrial fibrillation (AF) increases with aging, but the aging-associated electrophysiological changes of atrial myocardium are poorly understood. Methods and ResultsBased on the hypothesis that aging of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…This age-associated enhancement in carbachol-induced hyperpolarization may be due to a greater increase in I KACh (acetylcholine-induced potassium conductance) in aged atria, since the key mechanism for hyperpolarization of MDP is activation of I KACh through stimulation of muscarinic cholinergic receptors in the atria. More recently, Huang et al [5] used Langendorff-perfused rat hearts to record MAPs and ERPs of RA and LA epicardium from rats in 3 age groups: adult (7–8 months), middle-aged (13–15 months) and aged (over 2 years). Both MAPD 90 and ERPs were prolonged with age in RA (S1S1 = 400 ms) (Table 1), but in LA they were shorter in the aged group than in the other 2 groups.…”
Section: Substrate Changesmentioning
confidence: 99%
“…This age-associated enhancement in carbachol-induced hyperpolarization may be due to a greater increase in I KACh (acetylcholine-induced potassium conductance) in aged atria, since the key mechanism for hyperpolarization of MDP is activation of I KACh through stimulation of muscarinic cholinergic receptors in the atria. More recently, Huang et al [5] used Langendorff-perfused rat hearts to record MAPs and ERPs of RA and LA epicardium from rats in 3 age groups: adult (7–8 months), middle-aged (13–15 months) and aged (over 2 years). Both MAPD 90 and ERPs were prolonged with age in RA (S1S1 = 400 ms) (Table 1), but in LA they were shorter in the aged group than in the other 2 groups.…”
Section: Substrate Changesmentioning
confidence: 99%
“…4 In the MR dogs, regional LA conduction slowing and increased directional dependency, which allowed unidirectional conduction block and preferential pathways of conduction, may have accounted for the increased AF inducibility. 5 There is increasing evidence that AF is a predominantly a disease of the LA 6,7 and the role of the LA posterior wall (LAPW) in the mechanism of AF is well documented. In the chronic atrial pacing model in dogs the shortest AF cycle lengths (CLs) are found in the LAPW, 8 and patients with chronic AF.…”
mentioning
confidence: 99%
“…Therefore, it might be suitable to use older mice with a higher baseline AF inducibility in order to determine a possible protective effect of genetic manipulations presumed to cause a decreased inducibility rate. Because of the fact that a heterogeneously-slowed conduction velocity has been observed in the atria of the older animals, 30 and that atrial electrical remodeling is described as associated with age, 33 parasympathetic stimulation as a trigger for facilitating AF might not be necessarily needed to induce AF in older animals. However, additional parasympathetic stimulation seems to influence the stability of the induced AF episodes, because in the present study the duration of the AF episodes was longer after parasympathetic stimulation compared with baseline.…”
Section: Discussionmentioning
confidence: 99%